DROUGHT ANTICIPATION ON IRRIGATION LAND USING TRADE-OFF MODEL ON CASCADE RESERVOIR OPERATION - Azmeri Azmeri (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2011)
Abstract: An experiment based on literatute review and secondary data collecting to study and develop a software that can be operated by the users interactively and friendly, has been conducted. The results show that, on the trade – off curve based on the equal service level between energy and irrigation water, gained that the level to the energy demands of the smaller line with increased service levels, meet the demands of the irrigation water. Based on the trade-off analysis, however, for the dry year of 82.5%, show that both for these demands with the equal service level, were obtained.Keywords : software, trade-off curve, the equal service level, energy, irrigation, dry periodeAbstrak: Penelitian ini bertujuan untuk mengembangkan software yang dapat dioperasikan oleh pengguna (operator waduk) secara interaktif dan user friendly. Pada kurva trade-off berdasarkan tingkat layanan yang sama antara energi dan air irigasi, diperoleh bahwa tingkat layanan terhadap kebutuhan energi semakin kecil seiring dengan peningkatan tingkat layanan untuk pemenuhan kebutuhan air irigasi. Berdasarkan analisa trade-off, maka untuk tahun kering diperoleh sebesar 82,5% untuk kedua kebutuhan tersebut dengan tingkat layanan yang sama.Kata kunci : software, kurva trade-off, tingakt layanan yang sama, energi, irigasi, tahun kering.